Report - Coventry Trades and Labour Council, 11 May 1926 (1) (Coventry)
1926-05-11 "Report - Coventry Trades and Labour Council, 11 May 1926 (1)" [g0381001.jpg], 11 May 1926, Coventry Trades and Labour Council Local Organisation